West-Pontos black-glazed and red-figured wares: towards the end of the illusive attic supremacy? - Dupont, P. (Materiale și Cercetări Arheologice)
A programme of XRF analyses performed on a selection of b.g. and r.f. fine wares from Apollonia Pontica and from some other representative West Pontic settlements has evidenced a far less dominant position of Attic imports than generally assumed as well as a redistribution of the other ones into several separate units. The most significant one predominantly gathers finds from the Kalfata necropolis and thus might well be ascribable to local or regional manufacture.